Work Motivation and Career Autonomy as Predictors of Women’s Subjective Career Success in STEM - Schmitt, Miriam; Lauer, Sabine; Wilkesmann, Uwe (Acta Paedagogica Vilnensia, 2021)
The minority status of women in science, technology, engineering and mathematics (STEM) professions makes their successful career development difficult. Due to gender-specific challenges, career dissatisfaction contributes to women dropping out of STEM careers. Therefore, women’s subjective career success (SCS) is important to persist and progress in their STEM careers. This study analyzed the influence of different types of work motivation and the perceived career autonomy on SCS of women. Specifically, 318 women working in STEM professions in Germany completed a quantitative online questionnaire. Using an ordinary least squares regression for variables predicting SCS measured as career satisfaction, we found that an intrinsic work motivation positively affects women’s SCS. The perception of high career autonomy was related positively, and the perception of low career autonomy was related negatively to SCS. Unexpectedly, the findings also revealed the positive influence of income on women’s SCS. The findings show that intrinsic work motivation and high perceived autonomy are promoting factors for SCSs, which could also contribute to their retention in STEM professions.
Keywords: subjective career success; work motivation; career autonomy; women; gender; STEM